Perceived institutional support and its effects on student perceptions of AI learning in higher education: the role of mediating perceived learning outcomes and moderating technology self-efficacy - Jeilani, Abdulkadir; Abubakar, Said (Frontiers in Education, 2025)
The study aims at gaining insights into relationships between perceived institutional support and students’ perceptions of AI-supported learning. It also investigates the mediating role perceived learning outcomes and moderating effect of technology self-efficacy within this context. Research model was developed and validated based on Social Cognitive Theory (SCT) and the learning outcomes of students. Using quantitative research design and convenience sampling technique, 204 students from higher education institutions were included in the analysis. Data were analyzed using structural equation modeling (SEM) to test the hypothesized relationships. The results revealed that perceived institutional support significantly impacts students’ perceptions of AI-supported learning (β = 0.200, C.R. = 2.291, p = 0.022), technology self-efficacy (β = 0.492, C.R. = 9.671, p < 0.001), and learning outcomes. Additionally, technology self-efficacy was found negative moderating effect (β = −0.146, CR = −2.507, p = 0.012) the relationship between perceived institutional support and AI-supported learning perceptions. Perceived learning outcome partial mediated the relationship between perceived institutional support and students’ perceptions of AI-supported learning, with a direct effect of (β = 0.155, p < 0.001) and an indirect effect of (β = 0.539, p < 0.001), as evidenced by the confidence interval [0.235, 0.549]. These findings highlight the significant interplay of perceived institutional support, technology self-efficacy, and perceived learning outcomes in shaping students’ perceptions of AI in higher education, underscoring the importance of fostering supportive academic environments for effective AI integration. The theoretical and practical implications of the study are discussed.